ON THE PRINCIPLE OF THE MECHANISM OF ETHNIC GENEALOGY OF THE KHAZAR KING JOSEPH’S LETTER - Kulikova, O I; Abdusalamov, B B (History, Archeology and Ethnography of the Caucasus, 2017)
Interpretation of almost all the eponyms of Khazar King Joseph’s ethnic genealogy causes considerable difficulties. In this regard, O.A.Mudrak’s etymologization of these eponyms as well as the suggested principle of the mechanism of ethnic genealogy is of great interest. According to this researcher, all groups of the Khazar Khaganate population are presented in it, and presentation of their eponyms is given from west to east. However, this point of view provokes the following objections. Firstly, the given principle is clearly excessive for the letter of King Joseph, since all the main groups of the population of the Khazar Khaganate are presented in his list of the tributaries. Secondly, if the principle of the mechanism of O.A.Mudrak’s genealogy were observed, the eponym Khazar would not be in the seventh place, but in the first, or at least in the second place, after the descendants of the western Turks (they were probably Burtas). It follows that this genealogy is based on a quite different principle. We have proved a different interpretation of its mechanism: seniority of the eponyms presented in the genealogy is related to the degree of antiquity of the corresponding peoples, and some of these peoples had vanished into history by the 10th century. In the genealogy, these peoples might be, for example, the Huns, Goths or Avars. Of considerable interest is the fact that the eponym Bersil traces its origin to the proto-Nakh *borze-lvej “wolf”. In our opinion, this etymology can be supported by the following argument: one of the names of Khazaria - Arkan - can be etymologized according to the ancient Iranian languages as “wolves” (or “Wolves’ country”, cf. Scythian-Sarmatian varka “wolf”). This fact allows us to consider O.A. Mudrak’s etymology of the ethnonym Bersil as very promising. Keywords : Khazar king Joseph’s letter, ethnic genealogy, Khazar Khaganate, O.A. Mudrak.